Multiband observations of the Crab Nebula - Krassilchtchikov, A. M. (2017)
Results of simultaneous imaging of the Crab Nebula in the radio (JVLA), optical (HST), and X-ray (Chandra) bands are presented. The images show a variety of small-scale structures, including wisps mainly located to the north-west of the pulsar and knots forming a ring-like structure associated with the termination shock of the pulsar wind. The locations of the structures in different bands do not coincide with each other.